Europium complex with β-diketone and diphenylphosphinate ligands: Investigating its X-ray excited optical luminescent properties - Scarabello, Douglas [UNESP]; Garcia, Alessandro B.S. [UNESP]; Silva, Rodolpho A.N. [UNESP]; Moralles, Vagner A. [UNESP]; Bim, Luis F.B. [UNESP]; Pires, Ana M. [UNESP]; Davolos, Marian R. [UNESP]; Cebim, Marco A. [UNESP] (Elsevier, 2025)
Diphenylphosphinate ligand can effectively replace water molecules in coordination compounds with trivalent rare earth cations. This study investigates the synthesis and characterization of coordination compounds containing trivalent rare earth cations using β-diketones and diphenylphosphinate as ligands. The synthesized compounds yielded crystalline materials with distinct luminescent properties. Europium complexes exhibited intense red emission, underscoring their potential applications in displays and lighting. FT-IR spectroscopy confirmed the coordination of ligands to rare earth cations, while UV–Vis diffuse reflectance analysis provided insights into their electronic transitions. Analysis of excited state lifetimes and theoretical Anrad values suggested minimal presence or absence of deactivating groups like water molecules and Csp3-H bonds in the synthesized materials. The scintillation properties of these compounds were evaluated, indicating their suitability for scintillators and X-ray-induced photodynamic therapy. The [Eu-dpp] fragment efficiently absorbs X-rays and emits visible radiation, generating singlet oxygen (1O2) for therapeutic applications.
Keywords: Diphenylphosphinate; Energy conversion; Europium; Luminescence; β-diketones